Relationship between fidgety movement and frequency of movement toward midline: An observational study - Sermpon N. (2023)
Background: Infants show other movements and posture patterns during the fidgety movement period, including movement toward midline (MTM). Few studies have quantified MTM occurring during the fidgety movement period. Aims: This study aimed to examine the relationship between fidgety movements (FMs) and MTM frequency and occurrence rate per minute, from two video data sets (video attached to Prechtl video manual and accuracy data from Japan). Study design: Observational study. Subjects: It encompassed 47 videos. Of these, 32 were deemed normal FMs. The study amalgamated FMs that were sporadic, abnormal, or absent into a category of aberrant (n = 15). Outcome measures: Infant video data were observed. MTM item occurrences were recorded and calculated for occurrence percentage and MTM rate of occurrence per minute. The differences between groups for the upper limbs, lower limbs, and total MTM were statistically analysed. Results: Twenty-three infant videos of normal FMs and seven infant videos of aberrant FMs showed MTM. Eight infant videos of aberrant FMs showed no MTM, and only four with absent FMs were included. There was a significant difference in the total MTM rate of occurrence per minute between normal FMs versus aberrant FMs (p = 0.008). Conclusions: This study presented MTM frequency and rate of occurrence per minute in infants who showed FMs during the fidgety movement period. Those who showed absent FMs also demonstrated no MTM. Further study may need a larger sample size of absent FMs and information on later development.